vi = intial velocity
vf = final velocity
change of velocity = Vf - Vi
acceleration = change of velocity / change of time
acceleration = Vf-Vi ÷ t
at= vf - vi
displacement= average velocity X time
average velocity = Vi + Vf ÷ 2
d = (Vi + Vf ÷ 2 ) X t
WE SAY THAT 1st law
Vf= Vi + at
WE WILL CANCEL vf and but the rule
d = ( vi + vi + at ÷ 2) X t
= 2vit + at with power 2 ÷2
3rd law ---------- NOTE : ^ this mean with power too ok vf = vi+at by squaring vf^ = ( vi + at )^ vf ^ = vi^ + 2viat + a^t^ vf^-vi^=2viat+a^t^ = 2a(vit + half at^ )
THEN THE RULE IS note :^ this mean with power two 1) Vi + at = Vf first law 2) d = vit + half at ^ second law 3) Vf^- Vi^= 2ad third law
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Try to code in Latex.
Thanks!